Nos informamos sobre las diversas manifestaciones culturales de nuestra localidad - Díaz Julca, Elizabelt (2019)
The learning session entitled “Nos informamos sobre las diversas manifestaciones culturales de nuestra localidad” (We find out about the different cultural expressions in our locality) is aimed to develop the students’ personal and social skills by improving their competence to live together and participate democratically in achieving their common benefit and also their ability to interact with each other. This will,be accomplished by describing and sharing the cultural traits ( dancing, meals, clothing, etc.) that distinguish their locality or region from others. To work out this learning session, both the pedagogical and didactical processes related to the development of the students’ personal and social skills were taken into account in regards to the problem, analysis and decision making Strategies such as looking at pictures to describe people and activities were used according to the students’ age by means of guided observation to promote both individual and group participation. An assessment scale was also used as an evaluation instrument of the students’ performance while they were doing the task.